Очистка лактида методом перекристаллизации; Актуальные проблемы органической химии - Лукьянов А. Е. Александр Евгеньевич; Глотова В. Н. Валентина Николаевна; Бикмуллина (Иженбина) Т. Н. Тамара Николаевна; Новиков В. Т. Виктор Тимофеевич (2015, 2015)
Заглавие с экрана